2013
DOI: 10.1002/bip.22172
|View full text |Cite
|
Sign up to set email alerts
|

New small proteinase inhibitors from Capsicum annuum seeds: Characterization, stability, spectroscopic analysis and a cDNA cloning

Abstract: Recent results from our laboratory have previously shown the purification of a small serine proteinase inhibitor (PI), named CaTI1, from Capsicum annuum seeds. This work demonstrated the characterization of CaTI now named CaTI1, and the identification of two other small serine PIs, named CaTI2 and CaTI3, also present in these seeds. CaTI1 presented molecular mass of 6 kDa and pI value of ∼9.0. CaTI1 inhibited both trypsin and chymotrypsin with inhibition constants (Ki and Ki') of 14 and 2.8 nM for trypsin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Protease inhibitors were also detected by zymography (Figure 4B), and the results corroborate those from the trypsin inhibition assays (Figure 4A). Ribeiro et al [20] identified and purified a protein with trypsin inhibitory activity, called CaTI , from the C. annuum seed. This protein had the ability to permeabilize the plasma membrane of Saccharomyces cerevisia e and Candida albicans cells after 24 h of growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protease inhibitors were also detected by zymography (Figure 4B), and the results corroborate those from the trypsin inhibition assays (Figure 4A). Ribeiro et al [20] identified and purified a protein with trypsin inhibitory activity, called CaTI , from the C. annuum seed. This protein had the ability to permeabilize the plasma membrane of Saccharomyces cerevisia e and Candida albicans cells after 24 h of growth.…”
Section: Resultsmentioning
confidence: 99%
“…To stop the reaction, 100 μl of acetic acid was added. Afterward, photometric reading of the treatments was performed on the basis of released p -nitroanilide at wavelength of 405 nm [20].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that some pepper species have peptides with strong antimicrobial activity against bacteria [ 11 ], yeasts [ 12 ], filamentous fungi [ 13 ] and have inhibitory activity against α-amylases [ 14 ] and proteases [ 15 ]. The J1-1/GST defensin of Capsicum showed strong inhibitory activity against fungi of the genus Colletotrichum , which cause anthracnose, an infectious disease that despite the efforts to control it, remains an endemic disease, resulting in large reductions in annual yields worldwide [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction was interrupted by adding 100 µL of 30% acetic acid (v/v). The substrate hydrolysis was quantified by measuring the absorbance of released p ‐nitroaniline at 405 nm …”
Section: Methodsmentioning
confidence: 99%